Setting the scene: cross-sectional country comparisons of associations between young adult care and education, employment, and health outcomes in Europe - Mariona Lozano; Elisenda Rentería; Jeroen Spijker; Maike Van Damme; Giorgio Di Gessa; Rebecca Lacey; Baowen Xue; Anne McMunn (International Journal of Adolescence and Youth)
With increasing demand for informal carers, young adults are taking up care of dependent adults. However, early adulthood is the period in which most people invest in human capital and transition to employment. Being neither in employment nor in training (NEET) during this period may have long-term effects, increasing the risk of poor mental health. This study explores data from the third wave of the European Health Survey to better understand the situation of young adult carers (18-29 years old) in Europe. Using multilevel regression models, results indicate that, overall, those who care for dependent adults are more likely to be in NEET status (intensive caring), perceive bad health, and report worse mental health. However, country-level care resources did not affect the gap between carers and non-carers. Hence, cultural differences, or other forms of support, arise as the main role of country differences in the health risks of young adult carers.